The Authentic Status of Islamic Information Published on Social Media - Mr. Asif zaman; Dr. Qaisar Bilal; Dr. Rahman Ullah (Journal of Religion and Society, 2025)
In today's digital world, social media serves as a primary source of information, education, and entertainment. Islamic scholars and audiences utilize these platforms to access and share religious content, including fundamental Islamic teachings. However, social media platforms often lack proper editorial oversight, resulting in the rapid spread of unverified and inaccurate Islamic information. This poses significant challenges to religious understanding and social harmony. This study critically examines the authenticity of Islamic information shared on social media, with a specific focus on Facebook. Using a purposive sampling technique, we analyzed 20 religious posts from February 2024 for their authenticity against established Islamic scholarly sources, such as the Quran and Hadith literature. The findings of the study indicate a prevalence of weak, fabricated, and baseless Hadiths widely circulated on social media. Many posts incorrectly attribute fabricated content to Prophet Muhammad (PBUH), which can lead to potential misinformation among audiences. This study emphasizes the crucial need for authoritative verification and the importance of digital literacy. It calls for increased engagement from Islamic scholars and the development of reliable verification tools. Furthermore, the research advocates for awareness campaigns, rigorous content monitoring by social media platforms, and the establishment of accessible verification systems to ensure the authenticity of Islamic teachings shared online. This study underscores the collective responsibility of social media users, religious scholars, and digital platforms to safeguard the integrity of Islamic discourse in the digital age. Through critical evaluation and responsible sharing, it is possible to preserve the authenticity of Islamic teachings and promote informed religious engagement within the online community. Keywords: Islam, Social media, Fake, Information, Hadiths, Quran